Performance of castor (Ricinus communis) genotypes with normal and delayed seeding under irrigated and rainfed conditions - REDDY, P RAGHURAM; VANAJA, M; RAO, C HANUMANTHA; SANKAR, G R; VENKATESWARLU, S; EASTIN, J D (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season (kharif) 1991 with 9 genotypes ('RCP 5-2', 'Aruna', 'HC 6','HC8','VP1','J1 35','48-1', 'Sowbhagya' and 'JM 6') of castor (Ricinus communis L.) along with a control ('GCH4'), differing in plant stature and duration under 2 dates of seeding (28 June 1991 and 6 September 1991) each underirrigated and rainfed conditions. Reduction under rainted conditions Was higher for stem height, diameter and internodelength than under irrigated conditions in early genotypes. The reduction was much higher for medium and late durationgenotypes. Node number remained unchanged under both the situations. Under late-seeded conditions increase in stemheight but decrease in diameter was observed. No difference in days to flowering was observed for the genotypes SOWnon 28 June 1991 between irrigated and rainfed conditions, but for the genotypes sown on 6 September 1991 the floweringextended with late duration variety 'JM 6' producing no tertiaries. Though there was significant reduction in bothnumber and green area of the leaves, only few varieties like 'JI 35' andÂ·'Aruna' maintained large leaf area even underrainfed conditions under both normal and delayed seedings. The stem and leaf weight in varieties like 'JI 35', 'Aruna'and '48-1' was high under irrigated conditions and these varieties maintained their superiority even under rainfedconditions. The study indicated that different varieties gave high yield through different yield components; thoughcapsule number, capsule weight and seed number were the major components under both irrigated and rainted situations.A total yield reduction of 49% was observed while oil content was least influenced by the stress conditions.